2023
DOI: 10.1136/bmjopen-2022-065918
|View full text |Cite
|
Sign up to set email alerts
|

Effects of verbal violence on job satisfaction, work engagement and the mediating role of emotional exhaustion among healthcare workers: a cross-sectional survey conducted in Chinese tertiary public hospitals

Abstract: ObjectiveRecently, Chinese ministries and commissions have issued a series of policies and systems in response to violent injuries to doctors, physical violence have been managed to a certain extent. However, verbal violence has not been deterred and is still prevalent, it has not received appropriate attention. This study thus aimed to assess the impact of verbal violence on the organisational level and identify its risk factors among healthcare workers, so as to provide practical methods for verbal violence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 62 publications
1
3
0
Order By: Relevance
“…This estimate aligns closely with the results of a global systematic review, which found that 57.6% of healthcare workers experienced verbal abuse in the past year (19). In a similar study in China, more than a third (35.5%) the healthcare workers in tertiary public experienced verbal violence in the preceding year (20). The prevalence of verbal abuse among health workers is consistently high due to several factors.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This estimate aligns closely with the results of a global systematic review, which found that 57.6% of healthcare workers experienced verbal abuse in the past year (19). In a similar study in China, more than a third (35.5%) the healthcare workers in tertiary public experienced verbal violence in the preceding year (20). The prevalence of verbal abuse among health workers is consistently high due to several factors.…”
Section: Discussionsupporting
confidence: 86%
“…The prevalence of verbal abuse among health workers is consistently high due to several factors. First, the nature of the healthcare profession, which involves direct contact with patients and their families, can lead to heightened emotions and stress, increasing the likelihood of verbal abuse (20,21). Additionally, the hierarchical structure within healthcare organizations can contribute to power imbalances and create an environment where verbal abuse is more likely to occur, particularly targeting new or junior staff members (22).…”
Section: Discussionmentioning
confidence: 99%
“… 23 Without a sense of job security, some nurses have a negative attitude towards work, such as not wanting to work, reducing work enthusiasm, negatively dealing with work-related problems, being apathetic for patients and even resigning. Low work enthusiasm was closely associated with low work engagement; previous studies revealed that work engagement further directly affected job satisfaction, 24 and meanwhile, it played a mediating role in the relationship between nurses' sense of security and turnover intention. 25 In this study, nurses described that a low sense of security might increase the occurrence of nursing errors, which in turn would affect the sense of security.…”
Section: Discussionmentioning
confidence: 82%
“…In our study, nurses’ emotional exhaustion was at a moderately high level, slightly higher than in Yang’s findings [ 47 ]. It may be caused by the following: (1) The 72.6% of married nurses in this study, during the COVID-19 epidemic, had high job demands, worked long hours in a cordoned off environment, worked endless shifts and had difficulty balancing work-family and may have been highly emotionally internalized, leading to emotional exhaustion [ 48 ]; (2) Inadequate staffing, cancellation of breaks or coming to work even when sick, unsafe working environment, lack of support from work resources, resulted in the nurses’ frustration and disillusion with their work [ 49 ]; (3) Related research points out that COVID-19-related fear, panic, misinformation and misdirected anger can all lead to workplace violence, and that workplace violence damages nurses’ mental health with negative emotions such as anxiety and depression, increasing ego depletion and causing nurses to experience emotional exhaustion [ 50 , 51 ] .…”
Section: Discussionmentioning
confidence: 99%